The changing characteristics of talented soccer players - a decade of work in Groningen - Elferink-Gemser, M. T.; Huijgen, B. C. H.; Coelho e Silva, M.; Lemmink, K. A.P.M.; Visscher, C. (Journal of Sports Sciences, 2012)
Talent development programmes for professional soccer clubs aim to guide players towards professional level performance. We identify whether the intermittent endurance capacity of these players may have changed over time. Since the 2000/2001 competition season, the intermittent endurance capacity of players in the talent development programmes of two professional soccer clubs was measured annually. A total of 492 players participated, divided across seven age categories (under 13 (U13), U14, U15, U16, U17, U18, U19) and resulting in 953 measurements. Analyses of variance showed an improvement in intermittent endurance capacity from the 2000/2001 season to 2009/2010 of around 50% in all age groups (P<0.05). A possible explanation is the increased quantity and quality of training over the years. When identifying, developing and selecting young players, scouts, trainers and coaches have to be aware that the current level of soccer and its underlying performance characteristics such as intermittent endurance capacity are improving over time. This factor may have consequences for current young players aiming to make it to the top 10 years from now.